Nonequilibrium Phase Diagrams in a Multilayer Ising Ferrimagnet System: The Glauber Type Stochastic Dynamics Approach - Paran, Nejdet; Ertas, Mehmet (Elsevier, 2024)
Multilayer Ising ferrimagnet system is studied with nonequilibrium phase diagrams employing the Glauber stochastic dynamics approach. Firstly, nonequilibrium phase transition temperatures and their phase transition nature are investigated in detail. The study shows that the system displays both the second and first-phase transition behaviors. Then, it is determined that the essential phases of nonequilibrium phase diagrams consist of five phases (i1, i2, nm1, nm2, p), four mixed phases (i1+ p, nm1 +nm2, nm2 + p, i1 + nm2), and four special points (A, B, E, TP). Lastly, the study demonstrates that the dynamic magnetic characteristics of the system exhibit a significant dependence on the parameters of the Hamiltonian.
Keywords: Nonequilibrium Phenomena; The Glauber-Type Stochastic Dynamics; Multilayer Ising System; Nonequilibrium Phase Diagrams; 05.50.+q. 05.70.Fh. 64.60.Ht. 75.10.Hk